An overview of Covid-19 pandemic: immunology and pharmacology. Issue 5 (3rd September 2021) - Arif, Amin; Ansari, Sana; Ahsan, Haseeb; Mahmood, Riaz; Khan, Fahim Halim
ABSTRACT: In this review, we present an elaborate account of coronavirus in context to Covid-19 focusing on its origin, genome, life cycle, and immunology with a basic understanding of the disease and its cause. Further, the transmission, prevention and advances in therapeutics have also been discussed anticipating the possible outcomes in the near future. Moreover, the recently emerged unconventional approaches to this viral disease like drug repurposing, plasma therapy, nasal spray, and other preventive measures worldwide are studied for a long-term impact and relevance. Hence, this account on coronavirus and the ongoing pandemic serves a purpose of spreading awareness and to pass on relevant knowledge for a better chance to combat such unfortunate health crisis in future.